The Effect of Environmental Accounting on The Increase in Firm Value - Bahtiar Effendi (ADI Publisher, 2020)
This study aims to analyze the factors of environmental accounting which consist of material inputs, non-product output, compliance aspects, transportation aspects, other aspects, supplier assessment, and environmental complaints mechanisms to increase firm value. The sample in this study was 71 respondents from companies in Banten which were determined based on the purposive sampling method. Then the data were analyzed using multiple linear regression methods. The results showed that environmental accounting which is proxied by non-product output, other aspects, and environmental complaints mechanisms have a significant positive effect on increasing firm value. Furthermore, it was found that there was a significant negative effect between material input and supplier assessment on the increase in firm value. Also, it was found that the compliance aspect had a positive and insignificant effect on the increase in firm value and the transportation aspect had a negative and insignificant effect on the increase in firm value. Finally, the results of this study found that environmental accounting simultaneously has a significant effect on firm value.